2023
DOI: 10.1038/s41598-023-38565-0
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord tethering and syringomyelia after trauma: impact of age and surgical outcome

Abstract: Posttraumatic spinal cord tethering and syringomyelia frequently lead to progressive neurological loss. Although several studies demonstrated favourable outcome following spinal cord detethering with/without shunting, additional research is required as no clear consensus exists over the ideal treatment strategy and knowledge about prognostic demographic determinants is currently limited. In this investigation, we retrospectively investigated 67 patients (56 men, 11 women) who were surgically treated and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Our results revealed that age was significantly associated with the occurrence of spinal cord tethering, with older patients being more likely to develop this complication. This finding is consistent with previous studies suggesting that age-related changes in spinal cord morphology and tissue elasticity may predispose older individuals to an increased risk of tethering following trauma [8][9][10] . Moreover, older age has been linked to decreased regenerative capacity and delayed healing, potentially exacerbating the severity of tethering and complicating surgical intervention.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that age was significantly associated with the occurrence of spinal cord tethering, with older patients being more likely to develop this complication. This finding is consistent with previous studies suggesting that age-related changes in spinal cord morphology and tissue elasticity may predispose older individuals to an increased risk of tethering following trauma [8][9][10] . Moreover, older age has been linked to decreased regenerative capacity and delayed healing, potentially exacerbating the severity of tethering and complicating surgical intervention.…”
Section: Discussionsupporting
confidence: 93%